Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1002/jhrm.21259
|View full text |Cite
|
Sign up to set email alerts
|

EHR‐related medication errors in two ICUs

Abstract: The objective of this study was to describe the frequency, potential harm, and nature of electronic health record (EHR)-related medication errors in intensive care units (ICUs). Using a secondary data analysis of a large database of medication safety events collected in a study on EHR technology in ICUs, we assessed the EHR relatedness of a total of 1622 potential preventable adverse drug events (ADEs) identified in a sample of 624 patients in 2 ICUs of a medical center. Thirty-four percent of the medication e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 45 publications
(93 reference statements)
0
19
0
Order By: Relevance
“…The alarming statistic of this study is that 19% of the EHR usability-related events could have resulted in patient harm. A prospective study of medication safety among 624 patients in two ICUs of a medical center identified a total of1,622 preventable adverse drug events after EHR implementation 14 . Thirty-four percent of medication events were related to EHR technology; they included orders with missing information and accepted duplicate medication orders.…”
Section: Usability Problems Of Health It and Their Negative Impact mentioning
confidence: 99%
“…The alarming statistic of this study is that 19% of the EHR usability-related events could have resulted in patient harm. A prospective study of medication safety among 624 patients in two ICUs of a medical center identified a total of1,622 preventable adverse drug events after EHR implementation 14 . Thirty-four percent of medication events were related to EHR technology; they included orders with missing information and accepted duplicate medication orders.…”
Section: Usability Problems Of Health It and Their Negative Impact mentioning
confidence: 99%
“…Current studies on tEMR use in pharmacy education do not report using any adapted models or frameworks to guide information technology acceptance. Although it is known that EMRs impact the medication use process, best practices for incorporating EMRs into pharmacy practice and preparing students for future careers are currently unknown [17,18]. Since pharmacy students are an integral part of the healthcare system and EMRs are ubiquitous in healthcare today, we conducted a study to gain a better understanding of pharmacy students' early experience with a tEMR.…”
Section: Introductionmentioning
confidence: 99%
“…Although significant research has shown the value of HF/SE in improving the design of technologies, such as smart infusion pump and subsequent medication safety,(22, 45, 46) patient safety problems continue to occur related to poor HF design and technology implementation. (47, 48) Significant work remains to more systematically integrate HF/SE (e.g. usability) in designing health information technologies,(49) in particular among vendors,(50) including training of designers and implementers in human-centered design.…”
Section: Introductionmentioning
confidence: 99%